Pengaruh Perkembangan Teknologi Terhadap Etika Profesionalisme Notaris - Dwitriani, Arifah Ayundari; Santoso, Budi (Universitas Ekasakti, 2023)
Advances in information technology also open up opportunities and challenges for Notaries and require that Notaries not only be able to work manually but can also utilize technology-based information. A professional code of ethics is a norm established and accepted by a professional group that provides instructions to its members on how to act and act while guaranteeing the moral quality of the profession in the eyes of society. The writing method applied is Normative Legal research. The aim of this research is to find out how technological developments influence and what challenges notaries face. Based on the results of this research, several influences and challenges due to current technological developments on Notary ethics include: a) Using social media as a promotional event. b) The existence of an electronic signature to be used as evidence. c) Cyber ​​crimes against personal data protection.